Children as Agents of Sustainability: A Pathway to Teaching Environmental Literacy Based on Preschool Teachers’ Perspectives at Sumatra - Salma Rozana; Fatimah Purba; Sanggul Maharani Yessa; Rahayu Fuji Astuti; Ahsani Maulidina (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This explanatory sequential mixed-methods study investigates the perspectives of 89 early childhood teachers in Sumatra, Indonesia, regarding environmental literacy. Quantitative data were collected via an online questionnaire distributed through Google Forms, followed by qualitative data gathered through in-depth interviews conducted via Zoom. Descriptive statistics were used to analyse the quantitative data, while a thematic approach was applied to the qualitative findings. Three major themes emerged. First, teachers demonstrated a strong commitment to fostering environmental knowledge through experiential learning. They highlighted the importance of engaging children’s five senses and promoting active, reflective thinking to develop environmentally responsible behaviour that encompasses personal, social, and institutional dimensions. Second, key motivational factors for teaching environmental literacy included early instillation of environmental awareness, the cultivation of sustainable habits, nurturing care and love for nature, preparing environmentally conscious future generations, and supporting sustainability-oriented education initiatives. Third, the effectiveness of environmental literacy education was found to depend on both internal and external factors. Internally, teachers utilised strategies such as outdoor and play-based learning, project-based learning (PJBL), habit formation through place-based education, and digital media integration. Externally, successful implementation relied on collaboration with parents and communities, alongside institutional and governmental support. The study also revealed that teachers draw from ethnocentric, anthropocentric, and ecocentric perspectives when teaching about nature, indicating a strong sense of environmental place attachment. These insights underscore the need for contextually grounded teacher training, flexible curriculum development, and the production of locally relevant educational resources to enhance environmental literacy in early childhood education.